(3GdJagje dChGFd UfGYI GdJfLjes - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3Ef GdEMGWg HgjFI GdYGde hcjajg Tcd GdSeGA hGdCQV heG HjfgeG Ydi hLg GdCNHGQ GdeCNhPg HGdJbdjO fGaYg LOkG ai UfGYI GdJfLje s
(3BNQgG (B:s
(3abO LYdgG GdefJSHhf EdjgG aVdkG Yf GdefJajf YfgG s
(3ajgG YOO ef GdUhQ hGdQShes
(3eQbeI HGdCQbGe GdCaQfLjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B205s
Keywords: (3Gdadcs